Pelatihan Bantuan Hidup Dasar (BHD) untuk Meningkatkan Kesiapsiagaan Komunitas Karang Taruna di Kelurahan Kota Bambu, Jakarta Barat - Sari Mariyati Dewi Nataprawira; David Limanan; Alexander Halim Santoso; Muhammad Fikri Dzakwan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Cardiac arrest is a critical medical emergency with a high mortality rate that requires immediate and appropriate action to increase the chances of survival. One key factor in improving survival outcomes is the involvement of bystanders, particularly young people, in providing Basic Life Support (BLS). This community service activity was carried out to improve the knowledge and practical skills of youth organization members (Karang Taruna) in Kota Bambu Subdistrict, West Jakarta, in recognizing and responding to cardiac arrest using BLS procedures. The activity adopted the PDCA (Plan-Do-Check-Act) approach. The planning stage involved the preparation of materials and training tools for both theoretical and practical learning. The implementation phase included a 45-minute health education session covering the basics of BLS, especially cardiopulmonary resuscitation (CPR), followed by hands-on training. Participants were divided into small groups and guided through practical CPR simulations using manikins, facilitated by six trained nursing students. The activity was conducted on June 14, 2025, and attended by 57 participants, with 27 actively participating in the CPR practice session. The evaluation stage revealed a notable increase in the participants’ understanding and ability to perform CPR effectively. This indicates that community-based BLS training can be a powerful tool in improving emergency response at the grassroots level. In addition to raising awareness, the activity also empowered the youth as first responders in their community, strengthening their role in emergency preparedness and response. The follow-up stage emphasized the importance of sustainability through continued collaboration between local health professionals and community organizations. In conclusion, BLS education and training programs for youth can significantly enhance community resilience and are recommended for broader implementation in other regions.